Net zero carbon buildings: A review on recent advances, knowledge gaps and research directions - Nwe Ni Myint; Muhammad Shafique; Xiangming Zhou; Zhuang Zheng (Case Studies in Construction Materials)
As the building sector is a significant contributor to global greenhouse gas emissions and energy consumption, achieving net zero carbon buildings (NZCBs) is vital for reducing environmental impact and meeting global climate goals. This review synthesised recent advances in minimising embodied carbon and operational carbon, identified key research gaps, and proposed future research for achieving NZCBs. It investigates the challenges and opportunities across legislative, financial, cultural, technological, and stakeholder domains. Then, best practices in the decarbonisation of buildings, such as implementation of energy efficiency measures, utilisation of renewable energy sources, and adoption of circular economy principles are examined. Additionally, innovations in new building materials, such as Cross-Laminated Timber (CLT), Cold-Formed Steel (CFS), and Highly Sulfated Calcium Silicate Cement (HSCSC), were found to have substantial potential for reducing embodied carbon. Moreover, technologies like Photovoltaic (PV) panels and modular construction contribute to reducing operational emissions. This study emphasises the importance of comprehensive policies, public education, and collaborative stakeholder engagement in driving the transition to NZCBs. Furthermore, a variety of future research on low-carbon materials, energy efficiency, policies, upfront costs and comparative studies on net zero emissions between developed and developing nations are crucial for scaling sustainable practices globally. The study aims to support global decarbonisation efforts in the built environment by examining best practices, technological innovations, and strategic approaches. These findings highlight the need for continued research and development in sustainable building technologies and the importance of implementing effective policies to achieve a net zero carbon future.